Role of Pear Fruit Cuticular Wax and Surface Hydrophobicity in Regulating the Prepenetration Phase of Alternaria alternata Infection. Issue 5 (23rd March 2017) - Tang, Ying; Li, Yongcai; Bi, Yang; Wang, Yi
Abstract: The role of cuticular wax and the surface hydrophobicity of the fruit of the 'Zaosu' pear (Pyrus bretschneideri Rehd ) in regulating the prepenetration phase of Alternaria alternata infection were analysed in vivo and in vitro . Results showed that cuticular wax on an intact fruit surface, as well as wax extracts mounted on silanized glass slides or onion epidermis, favoured the formation of short, differentiated germ tubes and large numbers of appressoria (APP) or infected hyphae (IH). Dewaxed fruits or no wax extract mounted on in vitro surfaces, however, enhanced germ tube elongation and inhibited or delayed the formation of infection structure. High surface hydrophobicity resulting from cuticular wax also stimulated infection structure formation, as contact angle (hydrophobicity) was positively correlated with APP formation but negatively correlated with germ tube elongation. Alternaria alternata cutinase enzyme activity was also induced by cuticular wax, both in vivo and in vitro . These findings suggest that the chemical composition and hydrophobicity of pear fruit cuticular wax are essential in facilitating fungal invasion by regulating the growth and differentiation of A. alternata during the prepenetration phase.